Academic Stress, Emotional Intelligence and Social Support: A Study of Senior Secondary Students - Dr. Divita Sharma; Dr. Vishakha Saini (International Journal of Indian Psychȯlogy, 2025)
Academic Stress is found to be the highest among the adolescents. The stress and anxiety to excel academically, fulfill the expectations of parents creates an unpleasant psychological situation for adolescent leading to the academic stress. Emotional Intelligence is the ability to perceive feelings and emotions that helps in achieving the positive results by managing daily life pressures. Social Support is the comfort (physical and emotional) given by family, friends and it creates the sense of belongingness among individuals. The present study aims to find out the gender differences among the male and female adolescent students on the measures of Academic Stress, Emotional Intelligence and Social Support. The study comprises of 200 students from the Senior Secondary Schools of the Aligarh Muslim University, Aligarh. The data comprises of 100 (Science) and 100 (Commerce) stream students. Mean, SD and ANOVA were used to analyze results. The result showed significant mean difference among commerce and science stream students on the measures of Academic stress, Emotional Intelligence and Social support.